Effect of Combination Nature Sound Music Therapy with Positive Self Talk on Reducing Post Stroke Anxiety - Bisma Romanda Joki Pratama; Endang Caturini Sulistyowati; Dwi Ariani Sulistyowati (GLOBAL HEALTH SCIENCE GROUP, 2025)
Stroke is the second leading cause of death and the third cause of disability in the world. Post-stroke anxiety arises due to dependence due to physical disorders that affect life satisfaction. Post-stroke anxiety can increase the risk of recurrence, slow recovery and decrease quality of life. One of the efforts to reduce anxiety is the combination method of nature sound music therapy with positive self talk. This study aims to determine the effect of the combination of nature sound music therapy with positive self talk on the reduction of post-stroke anxiety. The study used a type of pre-experiment with a one-group pretest-posttests design.. Sampling with purposive sampling technique was 30 respondents. The instrument uses the Zung Self-Rating Anxiety Scale (ZSAS). The intervention was carried out 3 times of meetings and data analysis with the Paired T-Test. There was a difference in the level of anxiety before (44.67) and after (35.73) was given a combination intervention of nature sound music therapy with positive self talk with a p value of 0.000 < α 0.05 with a mean difference of 8.94 so that Ho was rejected and Ha was accepted. There is an effect of the combination of nature sound music therapy and positive self talk on reducing post-stroke anxiety.